Perbaikan Kurva Beban Harian pada Industri Kecil: Studi Kasus PT. X - Soewono, Arka D.; Kelvin, Dimas; Bachri, Karel Octavianus (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2024)
This paper presents the improvement of daily load and load balance curve of home-scale garment industry with the study case in PT. X. Research is started with load measurement on every machine, proceeded by plotting schedule of each machine. The next step is rescheduling daily load and per-phase load balancing. Initial data shows unbalance load sharing between phase with the average load of 4916 kW and standard deviation of 2077. After being rescheduled and phase rearrangement, the interphase load sharing is more balance, with the average load of 4903 kW and standard deviation of 952.